2011
DOI: 10.1177/002204261104100204
|View full text |Cite
|
Sign up to set email alerts
|

Age of Sexual Initiation, Psychiatric Symptoms, and Sexual Risk Behavior among Ecstasy and LSD Users in Porto Alegre, Brazil: A Preliminary Analysis

Abstract: Ecstasy and LSD use is widespread in large Brazilian cities, but there is limited information on their use among young, middle-class, club goers in Brazil. We conducted standardized face-to-face interviews with 200 male and female ecstasy and/or LSD users, focusing on drug use and sexual history, current risk behaviors, and psychiatric symptomatology. Participants with early sexual debut (before 14) were more likely to report lifetime use of marijuana and powder and crack cocaine than those with later sexual i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…We do not have objective data, such as a toxicology screen, to evaluate the degree of under-reporting of these activities, but a study performed on club-going adults in Porto Alegre showed that only 1.3% of men/women interviewed used crack in past 90 days, which is similar to rates endorsed by women on ACASI. 27 Furthermore, clinicians working in the hospital report that about 1% of newborns appear to be have symptoms of in utero drug exposure (approximately 4 each month of 400 births), which is also consistent with our results. 28 However, it is important to note that a prior study performed on pregnant women in the USA showed that when comparing ACASI to toxicology screens, there was significant underreporting of drug use.…”
Section: Discussionsupporting
confidence: 91%
“…We do not have objective data, such as a toxicology screen, to evaluate the degree of under-reporting of these activities, but a study performed on club-going adults in Porto Alegre showed that only 1.3% of men/women interviewed used crack in past 90 days, which is similar to rates endorsed by women on ACASI. 27 Furthermore, clinicians working in the hospital report that about 1% of newborns appear to be have symptoms of in utero drug exposure (approximately 4 each month of 400 births), which is also consistent with our results. 28 However, it is important to note that a prior study performed on pregnant women in the USA showed that when comparing ACASI to toxicology screens, there was significant underreporting of drug use.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests a link between earlier sexual initiation and illicit drug use behaviors, which is supported by the existing literature (Rosenbaum & Kandel 1990; Pechansky et al 2011). In addition, we noted that the age at sexual debut in our sample was higher than in studies among illicit drug users in other countries (Abdala et al 2012; Pechansky et al 2011), which was consistent with the fact that Chinese youth have a later onset of sexual activity in comparison to Western societies (Guo et al 2012)…”
Section: Discussionsupporting
confidence: 84%
“…Sexual debut in adolescence has been shown to be a strong predictor of illicit drug use in later life (Novoa et al 2005; Pechansky et al 2011). To date, there have been few attempts to investigate the relationship between age at sexual debut and age at drug initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Pechansky et al (2011) reported that early sexual debut was associated with lifetime cannabis use. However, this study was restricted to current ecstasy/LSD users and is thus not generalizable to the broader population.…”
Section: Introductionmentioning
confidence: 99%